Preliminary Insights into the Gut Microbiota of Captive Tigers in Republic of Korea: Influence of Geographic and Individual Variation - Beoul Kim; Saebom Lee; You-Jeong Lee; Yong-Myung Kang; Man Hee Rhee; Dongmi Kwak; Yong-Gu Yeo; Ju Won Kang; Taehwan Kim; Min-Goo Seo (Microorganisms, 2025)
The gut microbiome plays a crucial role in the health and physiology of tigers (Panthera tigris), influencing digestion, immune function, and overall well-being. While numerous studies have characterized the gut microbiota of domestic carnivores and some wild felids, comparative analyses across different tiger subspecies under varying environmental contexts remain limited. In this exploratory study, we investigated the gut microbiome diversity and composition of 15 captive tigers, including both Siberian (P. tigris altaica) and Bengal (P. tigris tigris) subspecies, housed in two different regions in Korea. Using 16S rRNA gene sequencing of fecal samples, we analyzed microbial diversity across multiple taxonomic levels. Preliminary analyses revealed significant differences in microbial composition between geographic locations, whereas sex-based differences appeared minimal. Alpha and beta diversity metrics demonstrated substantial inter-individual variability, likely influenced by regional and environmental factors. Given the small sample size and the confounding between subspecies and housing location, the findings should be regarded as preliminary and not generalized beyond this specific cohort. Nevertheless, these insights highlight the potential utility of gut microbiome profiling for health monitoring and management in captive-tiger populations. Future research incorporating larger, more diverse cohorts will be essential to validate these trends and clarify the roles of diet, health status, and enrichment in shaping the gut microbiota.